No signs of behavioral evolution of threespine stickleback following northern pike invasion. (7th April 2022) - Stevens, Dale R; Bardjis, Christina I; Baker, John A; Foster, Susan A; Wund, Matthew A
Abstract: Invasive predators often impose devastating selection pressures on native prey species. However, their effects can be regionally dependent and influenced by the local ecological conditions of their invaded habitats. Evolved behavioral phenotypes are important mechanisms by which prey adapt to the presence of novel predators. Here, we asked how behavior and behavioral plasticity of threespine stickleback ( Gasterosteus aculeatus ) populations have evolved following the introduction of the invasive predator, northern pike ( Esox lucius ). We examined the behavior of F1 offspring generated from three pike-free and three pike-invaded populations and measured how stickleback activity and plant use behaviors, and their plasticity, have evolved following pike introduction. To evaluate plasticity, we exposed juvenile stickleback to predator cues during their first year of development and then evaluated how this repeated exposure influenced behavioral responses to an artificial predation event. We found no overarching effect of pike in either evolved behaviors or behavioral plasticity, and no evidence for the presence of developmental plasticity. Furthermore, we found that depending on the phenotype, pike-invaded stickleback populations have either more or less among-population variation than pike-free populations. Our results suggest that evolution in response to invasive predators may be hidden by local adaptation when enough populations are studied. Abstract : In nature, selection often favors animals that have specific responses to predation encounters. However, unintuitively, sometimes selection can favor a lack of behavioral response when predators are abundant in their environment. We demonstrated that behavioral strategies of threespine stickleback populations experiencing predation from an invasive predator, northern pike, vary considerably in their behavioral responses, and that evolution in response to predation may be highly variable even within a species.